ADAPTASI MADRASAH DI DAERAH RENTAN KONFLIK SOSIAL - Arief Sukino; Erwin Erwin (Universitas Islam Negeri Ar-Raniry, 2019)
The existence and sustainability of madrasas are influenced by actors and the environment. The actor's ability to interpret the environment becomes a strategic point in strengthening the institution's existence. The meaning of the external internal environment can be shown in adaptability. This article discusses adaptation models carried out by madrasas in conflict-vulnerable areas with a qualitative approach. Based on the research, it was concluded that the existence and development of madrasas was carried out by the first method of Human Resource Configuration: the Multicultural Adaptation Model, which empowers teachers, administrative staff who are diverse in ethnic, customs and culture. second Madrasah Curriculum Reconstruction: An inclusive adaptation model that is in the academic field developing science majors at Aliyah madrasa, providing local mutants in Agriculture and Fisheries at MI level while in the non-academic field forming Drumband teams and becoming iconic for madrasas, thirdly Multicultural Idelogy that seeks internalized openness, respect, sympathy, tolerance and cooperation through contextual learning and integrated in each subject. in addition, internalization is carried out with social action activities